2016
DOI: 10.1007/s00464-016-4799-8
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of existing risk stratification guidelines for the evaluation of patients with suspected choledocholithiasis

Abstract: Existing guidelines performed suboptimally for predicting choledocholithiasis in our patient population, similar to other validation studies. These findings further underscore the importance of developing alternate risk stratification tools for choledocholithiasis, aiming to minimize unnecessary diagnostic ERCP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
45
2
10

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(62 citation statements)
references
References 14 publications
5
45
2
10
Order By: Relevance
“…Several risk‐stratification algorithms using predictors such as liver function tests (LFT), presence of cholangitis or pancreatitis, or findings on ultrasound (US) have been proposed . Recent studies have attempted to validate the commonly used guidelines of the American Society for Gastrointestinal Endoscopy (ASGE) for the prediction of CBD stones, but their conclusions have been somewhat conflicting . Furthermore, prediction algorithms other than that developed by ASGE have not been externally validated.…”
Section: Introductionmentioning
confidence: 99%
“…Several risk‐stratification algorithms using predictors such as liver function tests (LFT), presence of cholangitis or pancreatitis, or findings on ultrasound (US) have been proposed . Recent studies have attempted to validate the commonly used guidelines of the American Society for Gastrointestinal Endoscopy (ASGE) for the prediction of CBD stones, but their conclusions have been somewhat conflicting . Furthermore, prediction algorithms other than that developed by ASGE have not been externally validated.…”
Section: Introductionmentioning
confidence: 99%
“…Of the 92 patients with an intermediate risk for choledocholithiasis, 45 (48.9%) had stones on ERCP (accuracy 39.95%). Another study from the USA retrospectively analyzed 71 patients which met ASGE high-risk probability criteria for CBD stones [16] . Of these, only 39 (54%) were found to have a stone on ERCP.…”
mentioning
confidence: 99%
“…I remember that patients at high risk were defined as having a probability of choledocholithiasis >50%. Published series reported that patients with high-risk criteria for CBD stones had a documented stone/sludge in a range between 40 and 79.8% (average 60.1%) of the ERCPs [2,3,5,[14][15][16] . The majority of the published series concluded that the ASGE criteria demonstrated a probability of >50% of the patients having CBD stones.…”
mentioning
confidence: 99%
See 2 more Smart Citations